β-Selective One-Pot Synthesis of Acyl-C-Glycosides via Corey–Seebach Umpolung Reaction - Boehlich, G. Jacob; Schützenmeister, Nina (Synlett, 2019)
C-Glycosides are commonly used as carbohydrate mimics in drug development due to their stability against enzymatic and chemical hydrolysis. In this Synpacts article we elaborate on our fast and efficient β-selective approach towards protected and unprotected acyl glycosides. Application of a Corey–Seebach umpolung reaction enables the exclusive formation of the β-anomer of aromatic acyl-C-glycosides in good to excellent yields.1 Introduction2 C-Glycosylation of Benzylated Glycosyl Donors3 C-Glycosylation of Silylated Glycosyl Donors4 Conclusion
Keywords: carbohydrates; C-glycosylation; umpolung; Corey–Seebach reaction; natural products; scleropentasides